2005
DOI: 10.1089/ees.2005.22.427
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Permeate Flux Rate and Membrane Fouling in Dead-End Microfiltration of Primary Sewage Effluent

Abstract: Dead-end microfiltration was used to evaluate the permeate flux and fouling mechanisms by primary sewage effluent from a local wastewater treatment plant for seven polymeric membranes ranging in pore size from 0.2 to 0.8 m. Permeate flux rates were evaluated during separate filtration runs at transmembrane pressures of 1.03 and 2.06 bar and during a periodic increase in filtration pressure from 1.03 to 4.14 bar in a single run. The steady-state permeate flux rates were very similar for all pressures and pore s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The membrane resistance can also be estimated using the Kozeny‐Carman equation (Eq. 2) under the assumption that each membrane consists of closely packed spheres 24 …”
Section: Resultsmentioning
confidence: 99%
“…The membrane resistance can also be estimated using the Kozeny‐Carman equation (Eq. 2) under the assumption that each membrane consists of closely packed spheres 24 …”
Section: Resultsmentioning
confidence: 99%
“…FASP would be considered a form of dead-end filtration in which the feedstock is perpendicular to the membrane . In such a strategy, membrane fouling can be an issue, giving rise to reduced analyte recovery. , Electrofiltration can circumvent this by applying an electric field to oppose the motion of charged particles away from the filter . Cross-flow filtration is another strategy for sample purification wherein the fluid flows tangential to the dialysis membrane .…”
Section: Introductionmentioning
confidence: 99%
“…This study is an extension of previous research on the application of microfiltration in treating combined sewer overflows (CSOs) (Bendick et al, 2004;Modise et al, 2005), which demonstrated that a 0.2-lm membrane would be the most appropriate membrane for the treatment of CSO wastewater. This study focuses on the fouling pattern of microfiltration of primary and secondary effluents from municipal wastewater treatment plants on polymeric microfiltration membranes.…”
Section: Introductionmentioning
confidence: 85%